NEC simulation of a bidirectional antenna using a probe excited elliptical ring - Chawanonphithak, Krittaya; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2005)
This paper describes the characteristics of a bidirectional antenna using a probe excited elliptical ring. Based on the waveguide principle, a design of elliptical ring cross section that yields the propagation in dominant mode can be chosen and clarified by Numerical Electromagnetic Code (NEC). The quarter wavelength probe can accomplish matching condition. Subsequently, a decision of the ring length that obtains the desired directivity as well as the efficient radiation pattern, standing wave ratio (SWR), polarization, and bandwidth can be found by simulation. To investigate the characteristics of the proposed antenna for applying at the base stations, the wired grid model must be constructed. Using NEC simulation, the antenna characteristics can be carried out. The antenna prototype is fabricated and tested to verify the validity of our design method and the usefulness in Thai Mobile system operated at the center frequency of 1.92 GHz, The proposed antenna radiating bidirectional beam is suitable for narrow and long path service area with simple configuration and cost effective. © 2005 IEEE.
Keywords: Bidirectional antenna; Elliptical ring; NEC